1994
DOI: 10.1002/ajhb.1310060202
|View full text |Cite
|
Sign up to set email alerts
|

Somatic comparisons of urban and rural Russian boys, ages 6, 9, and 15 years, living in St. Petersburg and surrounding areas

Abstract: Somatic data were collected during September 1991 on 280 males, ages 6, 9, and 15 years, residing in urban St. Petersburg, Russia, and in rural regions surrounding the city. Comparisons are made between urban and rural groups for measures of body size and form, skinfold thicknesses, body mass index (BMI), and estimated arm muscle area (ARM). The data were analyzed in 2 (urban-rural) × 3 (age) analyses of variance, with an alpha level of P < 0.05. Age differences were evident for all measurements. A significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0
1

Year Published

1994
1994
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 11 publications
(8 reference statements)
0
3
0
1
Order By: Relevance
“…These diseases were less common in rural areas, so they had the most favorable values of mortality measures It is well-documented that social stratification, measured either by socioeconomic status of individual families or by residence in a population center of a particular size, is reflected in the physical growth and development of people, their health status, and some demographic variables. In particular, in many countries at present, slower rates of growth and maturation, and shorter stature, are observed among people living in rural villages rather than in urban centers (Bielicki et al, 1981(Bielicki et al, , 1988Bogin, 1988;Cameron et al, 1992Cameron et al, , 1993 Henneberg and La Velle, 1999;Hulanicka et al, 1990;Jedliń ska, 1985; Komlos and Kriwy, 2002;Pasquet et al, 1999;Peñ a et al, 2003;Spurgeon et al, 1994;Susanne, 1984;Tanner and Eveleth, 1976;Weber et al, 1995). These differences in growth and physical status are in general greater in poorer countries, while in countries having the highest standard of living they tend to disappear (e.g., Australia, Bogin, 1988;Susanne, 1984;Tanner and Eveleth, 1976).…”
mentioning
confidence: 96%
“…These diseases were less common in rural areas, so they had the most favorable values of mortality measures It is well-documented that social stratification, measured either by socioeconomic status of individual families or by residence in a population center of a particular size, is reflected in the physical growth and development of people, their health status, and some demographic variables. In particular, in many countries at present, slower rates of growth and maturation, and shorter stature, are observed among people living in rural villages rather than in urban centers (Bielicki et al, 1981(Bielicki et al, , 1988Bogin, 1988;Cameron et al, 1992Cameron et al, , 1993 Henneberg and La Velle, 1999;Hulanicka et al, 1990;Jedliń ska, 1985; Komlos and Kriwy, 2002;Pasquet et al, 1999;Peñ a et al, 2003;Spurgeon et al, 1994;Susanne, 1984;Tanner and Eveleth, 1976;Weber et al, 1995). These differences in growth and physical status are in general greater in poorer countries, while in countries having the highest standard of living they tend to disappear (e.g., Australia, Bogin, 1988;Susanne, 1984;Tanner and Eveleth, 1976).…”
mentioning
confidence: 96%
“…Therefore, data in Table 5 may actually underestimate the number of children receiving less than recommended amounts of energy. Using body weight data shown in Table 6, which were gathered on these subjects a t the same time as the dietary data (Spurgeon et al, 1994), rural subjects at age 6 years appeared to be at a n advantage in energy consumption compared to urban boys, but at ages 9 and 15, urban boys had greater intakes of energy per kilogram of body weight. Fedorova (1989) found that boys ages 16-17 years who were attending a rural trade school in the town of Volsk in the middle Volga area had energy intakes of 2,900-3,000 kcal per day, which compares fairly closely to the 2,858 and 3,261 kcal intakes of 15-year-old rural and urban St, Petersburg boys.…”
Section: Discussionmentioning
confidence: 99%
“…Анализ данных обследования детей Санкт-Петербурга и их сверстников из Ленинградской обл., проведенного в 1990-х гг. группой американских и российских ученых, выявил существенные различия в морфологических показателях, общей калорийности пищи, потреблении витаминов и микроэлементов, которые оказались достоверно выше у горожан [Spurgeon et al, 1994;Steele et al, 1994]. В последние годы специфика процессов физического развития детей города и села изучалась рядом исследователей в разных регионах России [Кабанов, 2005; Медведев и др., 2011; Османов Р.О., Омариева, Османов О.Р., 2013; Егорова и др., 2014; Филатова, 2014; Цыбульская и др., 2014], в т.ч.…”
Section: Introductionunclassified